Heat-induced colour changes of pine (Pinus pinaster) and eucalypt (Eucalyptus globulus) wood - Esteves, Bruno (2008)
Heat treatment of Pinus pinaster and Eucalyptus globulus wood was carried out by hot air in an oven for 2–24 h at 170–200 C and by steam in an autoclave for 2–12 h at 190–210 C. The colour parameters L*, a* and b* were determined by the CIELAB method on radial, tangential and transverse sections of untreated and treated wood, and their variation with regard to the treatment (DL*, Da* and Db*) were calculated in percent. For untreated eucalypt wood, lightness (L*) varied between 54.1 and 63.8% with a* between 7.4 and 8.5, and b* between 15.7 and 19.9. For untreated pine wood, L* varied between 67.3 and 76.1%, a* between 6.9 and 7.6 and b* between 16.3 and 24.1. Oven heat-treated wood became darker (DL* about 50% for 4% mass loss), and this was more for eucalypt wood under the same treatment conditions. In general, the contribution of red (a*) and yellow (b*) colour decreased with heat treatment. The transverse section of the two species darkened less for both the treatments with small differences between radial and tangential sections. Lightness decrease was related to chemical changes; with good correlations with glucose (R2 = 0.96), hemicelluloses (R2 = 0.92) and lignin (R2 = 0.86). As regards colour, the heat treatments showed an interesting potential to improve the wood quality for solid timber products from pine and eucalypt.